Zigzag materials: Selective interchain couplings control the coexistence of one-dimensional physics and deviations from it - J. M. P. Carmelo; P. D. Sacramento; T. Stauber; D. K. Campbell (Physical Review Research)
The coexistence in the low-temperature spin-conducting phases of the zigzag materials BaCo_{2}V_{2}O_{8} and SrCo_{2}V_{2}O_{8} of one-dimensional (1D) physics with important deviations from it is not well understood. The studies of this paper account for an important selection rule that follows from interchain spin states being coupled more strongly within the spin dynamical structure factor of such zigzag materials whenever they are connected by a specific symmetry operation of the underlying lattice. In the case of excited states, this symmetry operation is only a symmetry in spin space if no electronic spin flip is performed within the generation of such states. The corresponding selective interchain couplings both protect the 1D physics and are behind important deviations from it concerning the enhancement of the spectral-weight intensity of S^{zz}(k,ω). Strong evidence is provided that this justifies, beyond interchain mean-field theory and in contrast to 1D physics, the experimental low-energy dominance in both zigzag materials of the longitudinal nuclear magnetic resonance relaxation rate term 1/T_{1}^{∥} for the whole magnetic field interval of the spin-conducting phases. To further understand the role of selective interchain couplings concerning their contradictory effects in protecting the 1D physics and controlling deviations from it, the physical-spins scattering processes behind the experimentally observed sharp peaks in the dynamic structure factor components are investigated. Indeed, the experimentally observed Bethe strings in S^{+−}(k,ω) cannot be expressed in terms of configurations of usual spinons. We find that the line shape at and near the sharp peaks of the spin dynamic structure factor experimentally observed in BaCo_{2}V_{2}O_{8} and SrCo_{2}V_{2}O_{8} is fully controlled by unbound-unbound and unbound-bound scattering of singlet pairs of physical spins 1/2. Our results on both the role of selective interchain couplings in protecting the 1D physics and being behind deviations from it and on the dynamical properties being controlled by scattering of singlet pairs of physical spins 1/2 open the door to a key advance in the understanding of the physics of the spin chains in BaCo_{2}V_{2}O_{8} and SrCo_{2}V_{2}O_{8}.